(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This article discussed likely connections between spectacular logos and color. The process used the text Quartett by Heiner Müller as a reference and involved the observation of the Bahian production called Quarteto, carried out in 2014, through consultation of photography and video. Interpretations of what was seen on stage were mentioned, with the core theoretical foundation being provoked by Lee Watson, David Hays, and Linda Essig, touching on the notion of conception in the work of the theater designer. With this, we hoped to provoke theory through the artist’s praxis.